LO87: Influence of co-injuries on post-concussion symptoms after a mild traumatic brain injury. (May 2020) - Ouellet, V.; Boucher, V.; Beauchamp, F.; Neveu, X.; Archambault, P.; Berthelot, S.; Chauny, J.; de Guise, E.; Émond, M.; Frenette, J.; Lang, E.; Lee, J.; et al.
Abstract : Introduction: Each year, 3/1000 Canadians sustain a mild traumatic brain injury (mTBI). Many of those mTBI are accompanied by various co-injuries such as dislocations, sprains, fractures or internal injuries. A number of those patients, with or without co-injuries will suffer from persistent post-concussive symptoms (PPCS) more than 90 days post injury. However, little is known about the impact of co-injuries on mTBI outcome. This study aims to describe the impact of co-injuries on PPCS and on patient return to normal activities. Methods: This multicenter prospective cohort study took place in seven large Canadian Emergency Departments (ED). Inclusion criteria: patients aged ≥ 14 who had a documented mTBI that occurred within 24 hours of ED visit, with a Glasgow Coma Scale score of 13-15. Patients who were admitted following their ED visit or unable to consent were excluded. Clinical and sociodemographic information was collected during the initial ED visit. A research nurse then conducted three follow-up phone interviews at 7, 30 and 90 days post-injury, in which they assessed symptom evolution using the validated Rivermead Post-concussion Symptoms Questionnaire (RPQ). Adjusted risk ratios (RR) were calculated to estimate the influence of co-injuries. Results: A total of 1674 patients were included, of which 1023 (61.1%) had at least one co-injury. At 90 days, patients with co-injuries seemed to be at higher risk of having 3 symptoms ≥2 points according to the RPQ (RR: 1.28 95% CI 1.02-1.61) and of experiencing the following symptoms: dizziness (RR: 1.50 95% CI 1.03-2.20), fatigue (RR: 1.35 95% CI 1.05-1.74), headaches (RR: 1.53 95% CI 1.10-2.13), taking longer to think (RR: 1.50 95% CI 1.07-2.11) and feeling frustrated (RR: 1.45 95% CI 1.01-2.07). We also observed that patients with co-injuries were at higher risk of non-return to their normal activities (RR: 2.31 95% CI 1.37-3.90). Conclusion: Patients with co-injuries could be at higher risk of suffering from specific symptoms at 90 days post-injury and to be unable to return to normal activities 90 days post-injury. A better understanding of the impact of co-injuries on mTBI could improve patient management. However, further research is needed to determine if the differences shown in this study are due to the impact of co-injuries on mTBI recovery or to the co-injuries themselves.